Determination of radon concentrations of the Dikili geothermal area in western Turkey - Yarar, Y; Günaydi, T; Çelebi, N (OXFORD UNIV PRESS, 2006)
For this study, a geothermal area around Izmir-Dikili, located in the western part of Turkey, was chosen as a measuring site and the radon concentrations of environmental samples were determined. Indoor radon monitoring was performed for 3 months in dwellings located in different part of the region using passive CR-39 nuclear track detectors. The radon concentrations of water samples drawn from wells, municipal supplies, village fountains and spas in the area were measured using a liquid scintillation detector (Packard Tri-Carb 2770 TR/SL, A-277001). Soil samples collected from each location were analysed and Ra-226 concentrations were determined using a gamma ray spectrometer connected to an HPGe detector. Annual effective doses from radon inhalation and ingestion were calculated.
Keywords: Environmental Sciences & Ecology; Public, Environmental & Occupational Health; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging